Another new species (and it’s not over yet) of Phyllodytes Wagler, 1930 (Anura, Hylidae) from the Atlantic Forest of southern Bahia, northeastern Brazil - Santos, Laisa S.; Roseno, Rafaella S.; Solé, Mirco; Dias, Iuri Ribeiro (Zootaxa, 2023)
The genus Phyllodytes, endemic to the Atlantic Forest, stands out for its life cycle being closely associated with bromeliads. Since the 2000s, the number of species in the group has more than doubled and the number is still increasing, a fact proven here with the description of Phyllodytes iuna sp. nov. This species, herein described using morphological and molecular evidence, is endemic to the Atlantic Forest of southern Bahia, in the northern portion of the Atlantic Forest Central Corridor. Phyllodytes iuna differs from both its sister species and most of its congeners by the color pattern on the dorsum and by the presence of a single tubercle in the tibiotarsal region. The genetic distance for a fragment of the 16S gene ranged from 4.4% to 5.0% between Phyllodytes iuna and its sister species (P. brevirostris and P. edelmoi), and from 5.8% to 14.2% with its congeners. The description of a new species of Phyllodytes serves as a reminder that our understanding of the group’s diversity is far from complete. Despite the alarming rates of deforestation, the Atlantic Forest continues to hold significant untapped potential for unexplored biodiversity.